COUNSELING ON THE USE OF TELEMEDICINE TO IMPROVE HEALTH FOR SOCIETY - Agung Triayudi; Ikbal Danu Setiawan (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
This research aims to organize an outreach program regarding the use of telemedicine in improving access and quality of health services for the community. This outreach program is designed to provide knowledge and skills to the public about how to use telemedicine effectively, including understanding the platform, the types of services available, and how to consult a doctor online. The methods used in this service activity include a series of workshops, online seminars and interactive question and answer sessions, which were attended by participants from various levels of society. The education material was delivered by a team of experts consisting of health practitioners, academics and telemedicine application developers. Program evaluation was carried out through participant satisfaction surveys and analysis of increased knowledge about telemedicine before and after counseling. The results of this activity show a significant increase in public understanding of telemedicine, including its benefits, safety and how to use it. Participants stated that they felt more confident to use telemedicine services to meet their health needs. This program was also successful in identifying barriers faced by the community in accessing telemedicine services and providing recommendations for future improvements. This research emphasizes the importance of public outreach and education as the key to optimizing the use of health technology, especially telemedicine, in improving the accessibility and quality of health services. This community service activity provides important insights for the development of an inclusive and sustainable digital health strategy.